The anchoring effect in business - Bahník, Štěpán; Greiner, Ben; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
The habilitation thesis presents the contribution of the author to the literature on the anchoring effect. The first part of the work is an original text, which first introduces various explanations of the anchoring effect. Next, it summarizes the most important applications of the anchoring effect in business settings and reviews possible ways of reducing the negative impact of anchoring. Finally, it discusses shortcomings of the current theories of anchoring and provides a sketch of an alternative account. The second part of the work is composed of the author’s articles on the anchoring effect.
Vedoucí práce
Habilitační práce (doc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet